Population-based preventive measures aimed at reducing alcohol consumption: international practice and prospects for escalating measures in the Russian Federation - A. O. Myrzamatova; A. V. Kontsevaya; B. E. Gorny; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To conduct a review of international studies and guidelines on the implementation of population-based preventive measures aimed at reducing alcohol consumption, and identify measures recommended by the World Health Organization, which have the potential for use in the Russian Federation.Material and methods. We used the following databases: PubMed, Science Citation Index, Scopus, The Campbell Collaboration Library of Systematic Reviews. The review includes systematic and non-systematic studies of measures related to alcohol consumption. The effectiveness of the identified measures was assessed according to the following criteria: behavioral changes (consumption/sales/level); incidence changes; mortality changes.Results. According to international practice of population-based prevention, effective measures that can be implemented in the Russian Federation include reducing the blood alcohol concentration legal driving limit, increasing the minimum legal drinking age, a complete ban on alcohol advertising, and a further increase in excise taxes.Conclusion. In the Russian Federation, significant progress has been achieved in implementing alcohol restriction measures, which has led to a reduction in its consumption and related consequences. Despite this, levels of alcohol consumption remain high and the potential for introducing population-based measures to reduce it has not been exhausted.